MYC‐Sensitized Cuproptosis Combined With PTT to Remodel the Immune Microenvironment of Prostate Cancer - Yan Gao; Ji Liu; Jiahui Hu; Chuansheng Xu; Shiyu Mao; Chen Li; Xudong Yao; Shuo Shi (Advanced Healthcare Materials, 2026)
ABSTRACT Prostate cancer (PCa) is the most prevalent malignancy in men, often progressing to a more refractory form castration‐resistant prostate cancer (CRPC) after primary androgen deprivation therapy. Immunotherapy has brought new hope to PCa patients, but the immunosuppressive characteristics of PCa cells limit its efficacy. Cuproptosis, which can affect tumorigenesis, therapeutic resistance, and immune modulation has received significant attention recently. However, it is limited by insufficient copper ion (Cu 2+ ) concentration, hypoxia, and overexpression of glutathione (GSH) in tumors. To overcome these limitations, a targeted nanoplatform (CuS@MYC‐PEG‐FA) is fabricated to achieve a synergistic cuproptosis and immunotherapy. CuS@MYC‐PEG‐FA can not only promote reactive oxygen species (ROS) generation and Cu 2+ release, but also elicit a powerful antitumor immunity response. Meanwhile, the loaded c‐MYC inhibitor (MYCMI‐6) can reduce the expression of glutaminase and subsequently inhibit the generation of GSH, further sensitizing cells to cuproptosis effectively. Notably, cuproptosis combined with photothermal therapy (PTT) can turn the “cold” tumor properties of PCa into “hot” ones, leading to its sensitivity to anti‐programmed death ligand 1 (anti‐PD‐L1) immunotherapy. The results show that the combination of CuS@MYC‐PEG‐FA and PD‐L1 inhibitor treatment can significantly inhibit the development of PCa, providing a new strategy for the treatment of PCa.